40.3k views
3 votes
Convert to exponential form
log(5x)(2x-4)=3x+2

2 Answers

0 votes

Answer:

2x - 4 = 25x^2x^3x

Explanation:

log(5x)(2x-4)=3x+2

2x- 4 = (5x)^(3x+2)

2x - 4 = (5x)^3x * (5x)^2

2x - 4 = 25x^2x^3x.

User Dory Zidon
by
6.2k points
4 votes

Answer:

Exponential form:


(5x)^(3x+2)=2x-4

Explanation:


\log_\text{base}(?)=\text{exponent}

is equivalent to
(\text{base})^\text{exponent}=?

So
\log_(5x)(2x-4)=3x+2

is equivalent to


(5x)^(3x+2)=2x-4

User Kerry Jackson
by
6.0k points